Investigated Lateral Sphincterotomy Versus 2% Diltiazem Gel Local Application in the Treatment of Chronic Fissure in ANO - Meherzai, Barat Gul; Sadat, Gulaqa (International Journal For Research In Biology & Pharmacy, 2019)
An anal fissure is a split in the anoderm over the hypertrophied band of internal sphincter at the anal verge fissure is almost always located close to the midline of the anal canal; in men, 95% are near the posterior midline and 5% near the anterior midline, whereas in women, about 80% will be located posteriorly and 20% anteriorly. In this study we compare symptomatic relief, healing and side effects of topical 2% Diltiazem gel and lateral internal sphincterotomy in the treatment of chronic fissure in ANO. In this prospective trial, 58 surgical out patients and/or admitted patients with chronic fissure in ANO was randomly divided into Group 1 (Diltiazem gel) and Group 2 (internal sphincterotomy) with 25 patients in each Group. Patients were followed up at weekly intervals for six consecutive weeks and biweekly for subsequent 3 months. Fissure was completely healed in 85.45% of patients in Group 1 and in 96.60% in Group 2. The mean duration required for healing of fissure was 5.02 weeks in Group 1 and 3.8 weeks in Group 2. 65.00% patients were free from pain in Group 1 whereas 70.98 % patients were free from pain in Group 2. No patient had any side effects in either group.